Antidiabetic potential of medicinal plants and their active components - Salehi, Bahare; Ata, Athar; Kumar, Nanjangud V. Anil; Sharopov, Farukh; Ramírez-Alarcón, Karina; Ruiz-Ortega, Ana; Ayatollahi, Seyed Abdulmajid; Fokou, Patrick Valere Tsouh; Kobarfard, Farzad; Zakaria, Zainul Amiruddin; Iriti, Marcello; Taheri, Yasaman; et al. (MDPI, 2019)
Diabetes mellitus is one of the major health problems in the world, the incidence and associated mortality are increasing. Inadequate regulation of the blood sugar imposes serious consequences for health. Conventional antidiabetic drugs are effective, however, also with unavoidable side effects. On the other hand, medicinal plants may act as an alternative source of antidiabetic agents. Examples of medicinal plants with antidiabetic potential are described, with focuses on preclinical and clinical studies. The beneficial potential of each plant matrix is given by the combined and concerted action of their profile of biologically active compounds.